The Influence of Workload on Employee Performance Mediated and Moderated by Digital Communication (A Case Study at A Flour Mill in The Cilegon Area) - Lestari, Dini Fajar; Sanusi, Fauji; Imron, Ali (Sahabat Publikasi, 2025)
This study investigates the relationship between workload and employee performance, examining work stress as a mediating variable and digital communication as a moderating variable in one of the flour mills companies in Cilegon region. Using a quantitative approach, data were collected through questionnaires from 133 respondents and analyzed using SmartPLS version 4 software. The results indicate that workload has a significant negative effect on employee performance and a significant positive effect on work stress. Work stress negatively and significantly affects employee performance, confirming its mediating role between workload and performance. However, digital communication was found not to significantly moderate the relationship between workload and employee performance. These findings suggest the importance of managing workload and work stress, as well as optimizing digital communication supported by proper training and organizational culture to improve employee performance. This study provides practical contributions for management in the flour mills industry, especially in effective human resource management.